2021
DOI: 10.2147/amep.s305514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Problem-Based Learning and Lecture-Based Learning: Effect on Nursing Students’ Immediate Knowledge Retention [Response To Letter]

Abstract: I am very glad to hear from you and happy to see the letter of response from the author Rahul Penumaka showing interest in the publication "Comparison Between Problem-Based Learning and Lecture-Based Learning: Effect on Nursing Students' Immediate Knowledge Retention" Saying this I think I need to respond to some of the points raised:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Problem-and-lecture-based learning (PLBL) was designed as a novel instructional method in large classes (Figure 1), combining complementary strengths of PBL in reasoning under minimal guidance (Jiménez-Saiz & Rosace, 2019) and LBL in immediate retention of fundamental knowledge (Solomon, 2021) for students. Student discussion is essential in PBL, and classic PBL requires a small number of 7-10 students to be efficient (Jiménez-Saiz & Rosace, 2019).…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem-and-lecture-based learning (PLBL) was designed as a novel instructional method in large classes (Figure 1), combining complementary strengths of PBL in reasoning under minimal guidance (Jiménez-Saiz & Rosace, 2019) and LBL in immediate retention of fundamental knowledge (Solomon, 2021) for students. Student discussion is essential in PBL, and classic PBL requires a small number of 7-10 students to be efficient (Jiménez-Saiz & Rosace, 2019).…”
Section: Pedagogical Frameworkmentioning
confidence: 99%
“…Also, the advantages of PLBL over IPBL or LBL suggested the complementarity of IPBL and LBL. Likewise, a recent study reported that students unfamiliar with clinical practice had preferred LBL because of its remarkable effect on immediate knowledge retention over PBL (Solomon, 2021). A systematic review supported an eclectic system in which the pedagogical tools from LBL and PBL were used cooperatively in the best interest of education and satisfaction of students (Jiménez-Saiz& Rosace, 2019).…”
Section: Reflectionsmentioning
confidence: 99%